2012
DOI: 10.1007/8904_2012_145
|View full text |Cite
|
Sign up to set email alerts
|

β-Galactosidosis in Patient with Intermediate GM1 and MBD Phenotype

Abstract: A 5-year-old girl with clinical and biochemical phenotypes encompassing both GM1-gangliosidosis (GM1) and Morquio B disease (MBD) is described. Mild generalized skeletal dysplasia and keratan sulfaturia were consistent with a diagnosis of MBD, while developmental delay and GM1-specific oligosacchariduria were consistent with GM1 gangliosidosis. No observable b-galactosidase activity was detected in leukocytes, and two mutations, p.R201H (c.602G>A) and p.G311R (c.931G>A), were identified by gene sequencing. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…22 The p.Gly311Arg was described in a single case report of an individual presenting with developmental delay and Morquio B phenotype. 18 A similar presentation was seen in patient 6 of the present sample who also exhibited borderline achievement of the motor skills and speech delay.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…22 The p.Gly311Arg was described in a single case report of an individual presenting with developmental delay and Morquio B phenotype. 18 A similar presentation was seen in patient 6 of the present sample who also exhibited borderline achievement of the motor skills and speech delay.…”
Section: Discussionsupporting
confidence: 81%
“…Molecular testing of GLB1 gene identified 5 previously known missense mutations: p.Arg59His (rs72555392; c.176G>A; g.33114105C>T), 14 p.Phe107Leu (rs397515616; c.319T>C; g.33110389A>G), 15 p.Leu173Pro (rs397515617; c.518T>C; g.33106989A>G), 16 p.Arg201His (rs189115557; c.602G>A; g.33099712C>T), 17 p.Gly311Arg (rs368568171; c.1048G>A; g.33093274C>T), 18 and p.Thr500Ala (rs72555368; c.1498A>G; g.33055784T>C). 2 The other mutations comprise 1 known polymorphism, c.1233+8T>C (rs13093698; g.33063050A>G); 1 new neutral mutation, p.Pro152= (rs397515618; c.456A>T, g.33109723T>A); the known insertion, c.1622-1627insG (g.33055710_33055705insG) 19 ; and 2 previously undescribed missense mutations, p.Ile354Ser (rs397515613; c.1061T>G; g.33087619A>C) and p.Thr384Ser (rs397515614; c.1150A>T, g.33063141T>A).…”
Section: Resultsmentioning
confidence: 99%
“…Another aspect to take into account is that several mutations affecting GLB1 gene have shown intermediate phenotypes that make difficult to discern between GGM1 and Morquio B disease. 9,21,23 25…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect to take into account is that several mutations affecting GLB1 gene have shown intermediate phenotypes that make difficult to discern between GGM1 and Morquio B disease. 9,21,[23][24][25] Also, it is important to accomplish that some patients with Morquio B have been diagnosed in the adulthood, 21,26 indicating that the late detection of this disease could leave several patients without diagnosis. Actually, in this study, we found that 4 of our 5 patients were identified at an old age (more than 3 years old) and their initial diagnosis was not of a GLB1 deficiency, since they were thought to have Morquio A disease due to the skeletal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The common p.Arg201His detected at the heterozygous level has been correlated with the juvenile GM phenotype but it has also been detected in a 15-year-old Morquio B patient harbouring the mutation at the homozygous level [ 73 ]. Thus, phenotypes in compound GLB1 heterozygous genotypes sometimes remain difficult to predict [ 75 , 76 ]. In addition, the GLB1 gene polymorphic variants p.Arg521Cys, p.Ser532Gly, and p.Arg595Trp have been reported to be associated with beta-galactosidase enzymatic pseudodeficiency [ 77 ].…”
Section: Introductionmentioning
confidence: 99%